Pendampingan Psikososial pada Anak Korban Kekerasan Seksual di UPTD PPA Kota Bandung - Nur Aini, Erisa Dwi; Rini Hartini Rinda Andayani; Ella nurlela; Jhon Raphael Saragih (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
This study examines psychosocial assistance at the UPTD PPA in Bandung City. The purpose of this study was to describe: 1) Characteristics of informants, 2) Psychosocial assistance for child victims of sexual violence, 3) supporting and inhibiting factors for psychosocial assistance, and 4) Access to services for child victims of sexual violence at the UPTD PPA in Bandung City. This study used a descriptive qualitative research method and informant selection techniques with purposive sampling techniques. The data collection techniques used were (1) In-depth interviews, (2) observation, and (3) Documentation studies. The number of informants, namely key informants, consists of 2 social workers, 1 psychologist, and 1 legal expert or advocate. The results of this study found information related to psychosocial assistance, starting from physical, psychological, and social assistance with the process of receiving complaints, initial assessments, follow-up assessments, intervention planning, implementation of legal assistance interventions, mediation, monitoring, evaluation, and termination. Supporting factors for the mentoring process include relationships, flexibility of counseling session times, family psychoeducation, support from the DP3A office, free services, and material or skills assistance, even though they are not permanent, as well as technology. Inhibiting factors for the mentoring process are a lack of sources of social support, family or kinship relationships, vulnerable socio-economic conditions, time, and place. Access to services for child victims of sexual violence, including health services, legal services, and education services.